MEKANISME PEMBERIAN KREDIT BANK BRI KONVENSIONAL KANTOR CABANG PEKANBARU PADA USAHA PERIKANAN DI PEKANBARU - Misye Gusriani; Hendrik '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Research about BRI bank crediting mechanisms conventional Pekanbaru branch office on fisheries in Pekanbaru is held on June 2015 in Pekanbaru city Riau province. This research has a goal to know the factors that influence the fluency provision of credit in fisheries sector and identify problems that occur on credit fisheries. The method used in this research is field research that the resercher collect the data to the field directly. Based on the result of research is found the result of BRI bank crediting mechanisms conventional Pekanbaru branch office started from administration, briefing and business survey, consideration and realitation. The factor that influences credit granting fisheries is credit history some prospective customers previosly and the problems that is found is collateral.Key words: Trachinotus Blochii, Development, Production